Palestine and Jewish History : Criticism at the Borders of Ethnography - Boyarin, Jonathan (Book collections on Project MUSE., 1996)
This provocative and personal series of meditations on the Israeli-Palestinian conflict argues that it represents a struggle not as much about land and history as about space, time, and memory. Palestine and Jewish History enacts rather than reports on Boyarin's process of error, pain, impatience, uncertainty, self-criticism, intellectual struggle, and dawning awareness, challenging and engaging us in the process of discovery.